Epigenetic Regulations of Inflammatory Cyclooxygenase-Derived Prostanoids: Molecular Basis and Pathophysiological Consequences - Hedi Harizi (Mediators of Inflammation)
The potential relevance of prostanoid signaling in immunity and immunological disorders, or disease susceptibility and individual variations in drug responses, is an important area for investigation. The deregulation of Cyclooxygenase- (COX-) derived prostanoids has been reported in several immunoinflammatory disorders such as asthma, rheumatoid arthritis, cancer, and autoimmune diseases. In addition to the environmental factors and the genetic background to diseases, epigenetic mechanisms involved in the fine regulation of prostanoid biosynthesis and/or receptor signaling appeared to be an additional level of complexity in the understanding of prostanoid biology and crucial in controlling the different components of the COX pathways. Epigenetic alterations targeting inflammatory components of prostanoid biosynthesis and signaling pathways may be important in the process of neoplasia, depending on the tissue microenvironment and target genes. Here, we focused on the epigenetic modifications of inflammatory prostanoids in physiological immune response and immunological disorders. We described how major prostanoids and their receptors can be functionally regulated epigenetically and consequently the impact of these processes in the pathogenesis inflammatory diseases and the development of therapeutic approaches that may have important clinical applications.